The genus Sympetrum Newman, 1833 in Thailand, with description of S. thailandensis sp. nov. (Odonata: Libellulidae) - Makbun, Noppadon (Zootaxa, 2023)
The records of genus Sympetrum Newman, 1833 from Thailand were analysed. The unidentified Sympetrum sp. reported from Chiang Mai and Loei provinces in the past is confirmed as S. hypomelas (Selys, 1884) and additional provincial records of this species are also provided. Sympetrum thailandensis sp. nov. is described and figured based on the adult specimens of both sexes from Hin Tung, Muang, Nakhon Nayok province, Central Thailand. The new species belongs to infuscatum-group and is most similar to S. darwinianum (Selys, 1883). However, it is different from the congener by a combination of morphological and colouration characters. The key to species of Sympetrum known from Thailand is also presented.